2019
DOI: 10.2337/db18-0686
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Antigen Processing and Presentation Pathway Components Demonstrated by Transcriptome and Protein Analyses of Islet β-Cells From Donors With Type 1 Diabetes

Abstract: Type 1 diabetes studies consistently generate data showing islet b-cell dysfunction and T cell-mediated anti-b-cell-specific autoimmunity. To explore the pathogenesis, we interrogated the b-cell transcriptomes from donors with and without type 1 diabetes using both bulk-sorted and single b-cells. Consistent with immunohistological studies, b-cells from donors with type 1 diabetes displayed increased Class I transcripts and associated mRNA species. These b-cells also expressed mRNA for Class II and Class II ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
108
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 62 publications
3
108
1
1
Order By: Relevance
“…Immunostaining using pancreatic tissue showed that MHC class II and CIITA were not stained in non‐diabetic pancreatic islets, but were occasionally found in the islets patients with type 1 diabetes. Furthermore, CD68 + cells (macrophages) exist independently of CIITA + β‐cells, and it was shown that in this study, CIITA and insulin double positive cells were not macrophages that phagocytosed β‐cells.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Immunostaining using pancreatic tissue showed that MHC class II and CIITA were not stained in non‐diabetic pancreatic islets, but were occasionally found in the islets patients with type 1 diabetes. Furthermore, CD68 + cells (macrophages) exist independently of CIITA + β‐cells, and it was shown that in this study, CIITA and insulin double positive cells were not macrophages that phagocytosed β‐cells.…”
mentioning
confidence: 51%
“…Russell et al . approached this argument with a novel technique called transcriptome analysis using donor islets as samples.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Following FASTQ file generation in BaseSpace (Illumina), sequence files from bulk cell libraries were processed as described previously, 14 except that expected counts were filtered to include only genes with > 10 counts in at least three samples prior to submission to DESeq2 for differential gene expression analysis. Genes with at least a twofold change in expression and adjusted P values of < .01 were considered differentially expressed between pretransplant and posttransplant groups.…”
Section: Bioinformatics Analysesmentioning
confidence: 99%